Bioaccessibility and transformation pathways of phenolic compounds in processed mulberry (Morus alba L.) leaves after in vitro gastrointestinal digestion and faecal fermentation. (September 2019) - Yu, Yanfang; Zhang, Bing; Xia, Yuhui; Li, Hongyan; Shi, Xuping; Wang, Junwen; Deng, Zeyuan
Graphical abstract: Highlights: Heat treatment resulted in decrease of phenolics in mulberry leaves. Roasted mulberry leaves showed the highest bioaccessibility of phenolics. 50%−80% of the bioaccessible phenolics were dialysable. Phenolics degraded into low molecular weight compounds after faecal fermentation. Abstract: The changes of phenolic compounds from the freeze-dried, hot-air dried, roasted and steamed mulberry ( Morus alba L.) leaves during the in vitro digestion were investigated. Caffeoylquinic acids, quercitrin glycosides and kaempferol glycosides were the main compounds. After simulated gastrointestinal digestion, the bioaccessibility of phenolics was much higher in roasted samples than those in hot-air, dried and steamed samples. Approximately 50%–80% of the bioaccessible phenolics were dialyzable depending on the different processing methods. The freeze-dried samples contributed to the highest amount of bioaccessible phenolics, followed by hot-air dried and roasted ones. All the initial phenolics degraded rapidly and were not detected after 24 h of faecal fermentation, except that at 0.5 h the amount of isoquercitrin and astragalin were increased by 156.48% and 177.44%, respectively. Consequently, quercetin, kaempferol, dihydrocaffeic acid, 3-(4-hydroxyphenyl) propionic acid and 3-methoxyphenyl-acetic acid were formed at different time. Transformation pathways for phenolics in the faecal fermentation were proposed.